2013
DOI: 10.1002/chem.201300317
|View full text |Cite
|
Sign up to set email alerts
|

Forced Bonding and QTAIM Deficiencies: A Case Study of the Nature of Interactions in He@Adamantane and the Origin of the High Metastability

Abstract: Calculations within the framework of the interacting quantum atoms (IQA) approach have shown that the interactions of the helium atom with both tertiary, tC, and secondary, sC, carbon atoms in the metastable He@adamantane (He@adam) endohedral complex are bonding in nature, whereas the earlier study performed within the framework of Bader's quantum theory of atoms in molecules (QTAIM) revealed that only He---tC interactions are bonding. The He---tC and He---sC bonding interactions are shown to be forced by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 116 publications
0
27
0
Order By: Relevance
“…Despite the attractiveness of the concept of privileged exchange channels and its certain acceptance, we will show, however, that this concept is incomplete or even incorrect. The possible cause of the lack of confirmation and possible erroneousness of this concept will also be given.…”
Section: Introductionmentioning
confidence: 77%
“…Despite the attractiveness of the concept of privileged exchange channels and its certain acceptance, we will show, however, that this concept is incomplete or even incorrect. The possible cause of the lack of confirmation and possible erroneousness of this concept will also be given.…”
Section: Introductionmentioning
confidence: 77%
“…Recently, Pendás and his collaborators and then Tognetti and Joubert, and Dem'yanov and Polestshuk have made considerable progress in clarifying the reason for the presence of bond paths between pairs of bonded atoms. Namely, by decomposing the IQA‐based interatomic interaction energy on the electrostatic energy and the exchange‐correlation energy (see the Methodology section) the first authors have showed that the presence of a bond path is closely related to the latter of these two components, i.e., to the exchange‐correlation energy (or, more precisely, to the exchange energy).…”
Section: Introductionmentioning
confidence: 99%
“…The empirical observation of a homeomorphism between the density and the virial field actually served as a justification of the physical meaning of BCPs . Despite the report of exceptions, this homeomorphism does hold for all the molecules investigated in Ref. .…”
Section: Resultsmentioning
confidence: 91%